Adenosine Stress Cardiovascular Magnetic Resonance With Variable-Density Spiral Pulse Sequences Accurately Detects Coronary Artery Disease: Initial Clinical Evaluation - Salerno, Michael; Taylor, Angela; Yang, Yang; Kuruvilla, Sujith; Ragosta, Michael; Meyer, Craig H.; Kramer, Christopher M. (Circulation. Cardiovascular imaging, 2014)
Adenosine stress cardiovascular magnetic resonance perfusion imaging can be limited by motion-induced dark-rim artifacts, which may be mistaken for true perfusion abnormalities. A high-resolution variable-density spiral pulse sequence with a novel density compensation strategy has been shown to reduce dark-rim artifacts in first-pass perfusion imaging. We aimed to assess the clinical performance of adenosine stress cardiovascular magnetic resonance using this new perfusion sequence to detect obstructive coronary artery disease. Cardiovascular magnetic resonance perfusion imaging was performed during adenosine stress (140 μg/kg per minute) and at rest on a Siemens 1.5-T Avanto scanner in 41 subjects with chest pain scheduled for coronary angiography. Perfusion images were acquired during injection of 0.1 mmol/kg Gadolinium-diethylenetriaminepentacetate at 3 short-axis locations using a saturation recovery interleaved variable-density spiral pulse sequence. Significant stenosis was defined as >50% by quantitative coronary angiography. Two blinded reviewers evaluated the perfusion images for the presence of adenosine-induced perfusion abnormalities and assessed image quality using a 5-point scale (1 [poor] to 5 [excellent]). The prevalence of obstructive coronary artery disease by quantitative coronary angiography was 68%. The average sensitivity, specificity, and accuracy were 89%, 85%, and 88%, respectively, with a positive predictive value and negative predictive value of 93% and 79%, respectively. The average image quality score was 4.4±0.7, with only 1 study with more than mild dark-rim artifacts. There was good inter-reader reliability with a κ statistic of 0.67. Spiral adenosine stress cardiovascular magnetic resonance results in high diagnostic accuracy for the detection of obstructive coronary artery disease with excellent image quality and minimal dark-rim artifacts.